Fiber optic Fabry-Perot interferometer sensor: an efficient and fast approach for ammonia gas sensing - Kanawade, Rajesh; Kumar, Ajay; Pawar, Dnyandeo; Late, Dattatray; Mondal, Samir; Sinha, Ravindra K. (Journal of the Optical Society of America B-Optical Physics, 2019)
In this work, we propose and demonstrate a Fabry-Perot-interferometer-based polydimethylsiloxane (PDMS) and poly(methyl methacrylate) (PMMA)-composite-coated optical sensor for ammonia and volatile organic compounds (VOCs) detection at room temperature. The principle of sensing is based on change in the cavity length of the FP cavity in the presence of varied concentrations of gases, which results in changes in the total reflectance due to the shift in wavelength of an interference pattern. The sensing composite material was coated on a single-mode optical fiber by using a simple dip-coating technique and explored it for sensing. The ammonia and VOCs measurements were performed for concentrations ranging from 5 to 500 ppm. The corresponding sensitivity and limit of detection of the developed sensor for ammonia gas detection was observed of the order of around 4.16 pm/ppm and 4.8 ppm, respectively. The response and recovery times of the sensor were found to be of the order of 50 s and 10 s, respectively, for the ammonia gas. This sensor provides a simple, cost-effective, highly sensitive, and repeatable approach to measure ammonia gas and other VOCs at room temperature and could fulfill the demands of industrial applications. (C) 2019 Optical Society of America

Negative axicon tip-based fiber optic interferometer cavity sensor for volatile gas sensing - Kanavvade, Rajesh; Kumar, Ajay; Pawar, Dnyandeo; Vairagi, Kaushal; Late, Dattatray; Sarkar, Sudipta; Sinha, Ravindra K.; Mondal, Samir (Optics Express, 2019)
In this research work we demonstrated negative axicon optical fiber tip filled with Polydimethylsiloxane (PDMS) as a sensor platform for volatile organic gases detection at room temperature. The response of the sensor was measured with various Volatile Organic Compounds (VOCs) such as Chloroform, Hexane, Isopropanol, Acetone, Toluene and Methanol in the concentration ranging from 5 to 200 ppm. The corresponding sensitivity and limit of detection (LOD) of the developed sensor for the measured VOCs were observed between the order of around 23.7 to 3.2 pm/ppm and 0.84 to 6.10 ppm, respectively. The response and recovery time of sensor were found between the order of 30 to 57 seconds and 8 to 25 seconds respectively for the measured VOCs. Thermal stability of the developed sensor was also studied at 30-70 degrees C with intervals of 10 degrees C. The principle of sensing is based on change in the length of the Fabry-Perot Interferometric (FPI) cavity in the presence of varied concentrations of VOCs, which results in changes in the shift in wavelength of an interference pattern attributed to the change in PDMS filling the cavity length (swelling). The experimentally observed trends in the relative swelling of PDMS with VOCs are found in agreement with the theoretically calculated values obtained from the Hansen solubility parameter (HSP). The developed gas sensor has the potential to fulfill the demands of industrial applications.

Fabrication and evaluation of a spatially resolved fiber-optic probe for diffuse reflectance measurement for noninvasive diabetic foot ulcer diagnosis perspective - Kumar, Ajay; Hattale, Gangadhar; Pawar, Dnyandeo; Kanawade, Rajesh (Optical Engineering, 2024)
Timely diagnosis and monitoring of wound progression or healing are key to improving the long-term outcome of diabetic foot ulcers (DFU). Diffuse reflectance spectroscopy (DRS) has the potential to noninvasively diagnose the DFU in real time, as it detects changes in local blood volume fraction and oxygenation state level that occur when tissue becomes diseased or ulcerated. Since foot soles have a thicker epidermis and deeper blood vessels/capillaries than other parts of the body, a spatially resolved fiber-optic probe (SRFP) is needed to detect the optimal spatially resolved diffuse reflectance (SRDR) signal from the local site of the ulcer for DFU diagnosis. Therefore, herein, an SRFP consisting of a linear array of seven 400-mu m fibers with detector-source (D-S) fiber separation (rho) ranging from 0.8 to 4.8 mm was designed, fabricated, tested, and evaluated for SRDR measurement from a standard reflectance plate of barium sulfate (BaSO4) and foot sole of 27 healthy human subjects. The variation in SRDR spectra for each detector and source fiber pair measured with BaSO4 was found to be less than 1.6%. In-vivo measurements from the foot sole demonstrate that the fabricated probe has the ability to spatially resolve and distinguish the SRDR spectra from sites, namely, the fifth metatarsal, ball of great joint, calcaneum, and great toe. Experimentally and theoretically, the detector and source fiber pair of rho=1.6 and 2.4 mm were optimal for SRDR measurements from a human foot. To evaluate and validate the performance of SRFP in a context relevant to DFU diagnosis, further SRDS measurements were performed on the solid tissue phantoms that mimic the optical properties of the normal and diabetic foot sole, and their results are statistically found different. Preliminary results suggest that developed SRFP can be explored for DRS measurement from foot ulcer patients to confirm its potential clinical applicability.
Keywords: diabetic foot ulcer; diffuse reflectance spectroscopy; foot sole; spatially resolved fiber-optic probe; tissue phantom

Polymeric PEI/PEG coated optical fiber fabry-perot interferometer for CO2 detection - Pawar, Dnyandeo; Lo Presti, Daniela; Lemma, Enrico D.; Rainer, Alberto; Kumar, Ajay; Kanawade, Rajesh; Silvestri, Sergio; Schena, Emiliano; Massaroni, Carlo (IEEE Sensors Journal, 2024)
Monitoring carbon dioxide (CO2) gas is essential for numerous applications, but the detection of CO2 in miniaturized devices presents significant challenges. In this study, a polyethyleneimine/poly(ethylene glycol) (PEI/PEG) coated optical fiber Fabry-Perot interferometer (FPI) and its charge transfer process toward CO2 are investigated. Scanning electron microscopy and Fourier transform infrared spectroscopy were used to analyze the surface morphology and vibration bands of the PEI/PEG composite. The PEI/PEG composite Fabry-Perot (FP) cavity of length similar to 13 mu m is coated at the distal end of the single-mode fiber using a dip coating technique. A highly sensitive optical and low-cost FPI probe fabrication has displayed a linear sensitivity of 17.10 nm/% in the range of 0.31%-1.25% CO2 gas. The response and recovery times of the sensor are in a few tens of seconds. The enhanced performance of the sensor is primarily due to the protonation and charge transfer between CO2 gas molecules and PEI/PEG composite. Due to low-cost fabrication and high sensitivity, this FPI sensor can be used in a range of potential applications in bioprocessing, healthcare, and environmental monitoring.
Keywords: dip coating; Fresnel's reflection; Interference; monitoring; Optical fiber sensors; Optical fibers; polymer composite; Polymers; refractive index; sensitivity; Sensor phenomena and characterization; sensors; swelling; Temperature sensors

Real-time estimation of blood oxygenation parameters from human foot sole during leg elevation: a preliminary study with diffuse reflectance spectroscopy - Kumar, Ajay; Lohchab, Viney; Pawar, Dnyandeo; Someshwar, Vimal; Mathe, Vikas; Husale, Sudhir; Kanawade, Rajesh (Optics and Laser Technology, 2025)
This study investigated the applicability of diffuse reflectance spectroscopy (DRS) for real-time and non-invasive measurement of blood oxygenation parameters (BOPs) such as reduced hemoglobin (RHb), oxyhemoglobin (HbO(2)), and oxygen saturation (SO2) from human foot sole during leg elevation. Seventeen (17) healthy male subjects aged between 21 to 39 years were included in this study. Diffuse reflectance spectra were recorded from measurement sites namely the 5th metatarsal, ball of great joint, calcaneum, and great toe of the human foot sole w.r.t. leg elevation angles such as 0(0), 15(0), 30(0), 45(0), and 60(0), respectively. The localized BOPs were derived from the recorded spectra. In addition, blood hemodynamic parameters (BHPs) such as heart rate (HR), SO2, perfusion index (PI), systolic blood pressure (SBP), and diastolic blood pressure (DBP) were also measured for each elevating angle. To study and assess the changes in BOPs and BHPs w.r.t. leg elevation, a One-way ANOVA test followed by a Tukey HSD post-hoc test was performed. We observed a statistically significant increase in RHb (p < 0.001) and a decrease in HbO(2) (p < 0.001) after 45 degrees of leg elevation, however, there was no statistically significant difference in SO2 (p = 0.74) and HR (p = 0.84) for each measurement site w.r.t. leg elevation, respectively. Furthermore, PI (p < 0.01), ankle SBP (p < 0.001) and DBP (p < 0.001) were decreased w.r.t. leg elevation. The obtained results are in agreement with the literature. The preliminary results suggest that DRS has the potential for real-time estimation of BOPs from the local sites of healthy human foot soles during leg elevation. Thus, it opens the possibility of DRS to monitor and evaluate the diagnosis and treatment of ischemia and edema during leg elevation of patients through BOPs measurement.
Keywords: diabetic foot ulcer; diffuse reflectance spectroscopy; Leg elevation; Oxygen saturation; Oxyhemoglobin; Reduced hemoglobin